2013
DOI: 10.1074/jbc.m113.487538
|View full text |Cite
|
Sign up to set email alerts
|

Direct Inhibition of Gcn5 Protein Catalytic Activity by Polyglutamine-expanded Ataxin-7

Abstract: Background: Polyglutamine expansion of the ataxin-7 protein, a subunit of the SAGA (Spt-Ada-Gcn5-acetyltransferase) complex, causes spinocerebellar ataxia type 7. Results: Polyglutamine-expanded ataxin-7 aberrantly binds to SAGA, affecting Gcn5 acetyltransferase activity at SAGA-regulated genes. Conclusion: Ataxin-7 exhibits a dominant-negative effect on Gcn5 catalytic activity in vivo. Significance: We show a direct dominant effect of polyglutamine-expanded ataxin-7 on SAGA acetyltransferase function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…The human DUB module subunit Ataxin7 (orthologous to yeast Sgf73) contains a region that can undergo poly‐glutamine expansion, causing the disease spinocerebellar ataxia type 7. Human Ataxin7 can partially complement a SGF73 deletion, but the Poly Q form inhibits HAT activity in vivo and in vitro (McMahon et al , ; Palhan et al , ; Burke et al , ). Here, we have shown that mutations in the DUB module subunit Sgf73 have modest effects on SAGA nucleosomal HAT activity and stability of the HAT module within SAGA.…”
Section: Discussionmentioning
confidence: 99%
“…The human DUB module subunit Ataxin7 (orthologous to yeast Sgf73) contains a region that can undergo poly‐glutamine expansion, causing the disease spinocerebellar ataxia type 7. Human Ataxin7 can partially complement a SGF73 deletion, but the Poly Q form inhibits HAT activity in vivo and in vitro (McMahon et al , ; Palhan et al , ; Burke et al , ). Here, we have shown that mutations in the DUB module subunit Sgf73 have modest effects on SAGA nucleosomal HAT activity and stability of the HAT module within SAGA.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, the deletion of Gcn5 impairs the association of the DUB module with SAGA (Atanassov et al, 2009), while in yeast, the full deletion of Sgf73 compromises the HAT activity, which can be restored by expressing human ATXN7 (McMahon et al, 2005). Furthermore, an ATXN7 carrying a 60 glutamine repeat to mimic the human SCA7 disease was described to bind to a recombinant Gcn5/ada2/ada3 complex and to decrease its HAT activity (Burke et al, 2013). The spatial proximity of the HAT and DUB modules does not contradict this observation since a long and unstructured polyQ stretch could interfere with the HAT catalytic or regulatory activities or with the nucleosome recognition functions.…”
Section: Position Of the Dub Modulementioning
confidence: 96%
“…Poly(Q) expansions in ATXN7 could affect either of these activities. Previous studies provided conflicting evidence regarding the effects of ATXN7-poly(Q) on the activity of Gcn5, the catalytic subunit of the histone acetyltransferase (HAT) module (8)(9)(10)(11). The loss of Gcn5 accelerates cerebellar Purkinje cell and retinal degeneration in a SCA7 mouse model, indicating that Gcn5 functions are pertinent to disease progression (12).…”
mentioning
confidence: 99%